2011
DOI: 10.5194/acp-11-11733-2011
|View full text |Cite
|
Sign up to set email alerts
|

Individual particle analysis of aerosols collected under haze and non-haze conditions at a high-elevation mountain site in the North China plain

Abstract: The North China plain is a region with megacities and huge populations. Aerosols over the highly polluted area have a significant impact on the regional and global climate. In order to investigate the physical and chemical characteristics of aerosol particles in elevated layers there, observations were carried out at the summit of Mt. Tai (1534 m a.s.l.) from 19 to 28 April, 2010, when the air masses were advected from the east (phase-I: 19–21 April), from the south (phase-II: 22–25 April), and from the northw… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(43 citation statements)
references
References 61 publications
2
41
0
Order By: Relevance
“…In addition, these S-rich particles were internally mixed with primary OM particles at the T2 site (Figure 2b-d), thereby suggesting that OM particles become more aged during long-range transport. Compared with haze particles collected in the North China Plain, our study did not observe fly ash and metal, but more abundance of OM-dominated particles [23,24]. As a result, we can exclude regional contribution from emissions of heavy industries and coal-fired power plants in upwind areas.…”
Section: Discussionmentioning
confidence: 81%
“…In addition, these S-rich particles were internally mixed with primary OM particles at the T2 site (Figure 2b-d), thereby suggesting that OM particles become more aged during long-range transport. Compared with haze particles collected in the North China Plain, our study did not observe fly ash and metal, but more abundance of OM-dominated particles [23,24]. As a result, we can exclude regional contribution from emissions of heavy industries and coal-fired power plants in upwind areas.…”
Section: Discussionmentioning
confidence: 81%
“…The growth processes can be enhanced by the internally mixed particles in haze layers (Li et al, 2011a). In addition, transmission electron microscopy (TEM) is an important technique for investigating the physical and chemical properties and mixing state of individual aerosol particles in HF episode (Li et al, 2011a;Posfai and Buseck, 2010;Ueda et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Fu et al (2012) observed four types of carbonaceous aerosols in the Shanghai atmosphere, and found that most of the particles were coated with secondary organic aerosols. Based on transmission electron microscopy, Li et al (2011b) also found more fractions of internally mixed EC particles in the polluted air of northern China. Single-particle soot photometer measurements revealed that the number fraction of internally mixed EC was highly variable and could be as high as ∼ 70 % in the PRD region, while the detailed information on mixing state is limited by this instrument (Huang et al, 2011(Huang et al, , 2012.…”
Section: G Zhang Et Al: Mixing State Of Individual Submicron Carbonmentioning
confidence: 99%